Ramon Flour (Brosimum alicastrum Swartz) Ameliorates Hepatic Lipid Accumulation, Induction of AMPK Phosphorylation, and Expression of the Hepatic Antioxidant System in a High-Fat-Diet-Induced Obesity Mouse Model - Trinidad Eugenia Cu-Cañetas; Laura A. Velázquez-Villegas; Mariana Manzanilla-Franco; Teresa del Rosario Ayora-Talavera; Juan José Acevedo-Fernández; Enrique Barbosa-Martín; Claudia C. Márquez-Mota; Adriana M. López-Barradas; Lilia G. Noriega; Martha Guevara-Cruz; Ana Ligia Gutiérrez-Solís; Azalia Avila-Nava (MDPI AG, 2023)
Excessive consumption of fat and carbohydrates, together with a decrease in traditional food intake, has been related to obesity and the development of metabolic alterations. Ramon seed is a traditional Mayan food used to obtain Ramon flour (RF) with high biological value in terms of protein, fiber, micronutrients, and bioactive compounds such as polyphenols. However, few studies have evaluated the beneficial effects of RF. Thus, we aimed to determine the metabolic effects of RF consumption on a high-fat-diet-induced obesity mouse model. We divided male BALB/c mice into four groups (n = 5 each group) and fed them for 90 days with the following diets: Control (C): control diet (AIN-93), C + RF: control diet adjusted with 25% RF, HFD: high-fat diet + 5% sugar in water, and HFD + RF: high-fat diet adjusted with 25% RF + 5% sugar in water. The RF prevented the increase in serum total cholesterol (TC) and alanine transaminase (ALT) that occurred in the C and HFD groups. Notably, RF together with HFD increased serum polyphenols and antioxidant activity, and it promoted a decrease in the adipocyte size in white adipose tissue, along with lower hepatic lipid accumulation than in the HFD group. In the liver, the HFD + RF group showed an increase in the expression of β-oxidation-related genes, and downregulation of the fatty acid synthase (Fas) gene compared with the HFD group. Moreover, the HFD + RF group had increased hepatic phosphorylation of AMP-activated protein kinase (AMPK), along with increased nuclear factor erythroid 2-related factor 2 (NRF2) and superoxide dismutase 2 (SOD2) protein expression compared with the HFD group. Thus, RF may be used as a nutritional strategy to decrease metabolic alterations during obesity.